Gambaran Pelaksanaan Deteksi Dini Inspeksi Visu L Asam Asetat (IVA) Terhadap Kejadian Kanker Serviks Pada Wanita Usia Subur Di Puskesmas Purwojati - Sawitri Dewi (Stikes Muhammadiyah Klaten, 2019)
Cancer is a health problem for people around the world, according to data from the World Health Organization (WHO), cervical cancer contributes 12% of all cancers affecting women and is the second leading cause of death for women in Indonesia after breast cancer. Every day, it is estimated that 41 new cases occur and 20 women die from the disease. Because of the high risk factors for this disease, women should do early detection, one of which is the Acetic Acid Visual Inspection (IVA) method. This method is relatively simple, comfortable and practical. IVA is a method for early detection of cervical cancer using 3-5% acetic acid, and has an accuracy of 90%. The purpose of this study was to determine the implementation of early detection of IVA on the incidence of cervical cancer in women of childbearing age in the Purwojati Health Center, Banyumas Regency. The research design used an analytic survey with a cross sectional approach. The sampling technique used accidental sampling. Data processing was carried out by using the Chi-Square (X2) test. The results showed that the incidence of cervical cancer was 15%, most women of childbearing age did not perform early detection of cervical cancer with the IVA method because of ignorance and shame.